Surgical vs. non-surgical management of temporomandibular joint disorders: Clinical outcomes - Mohammad K Alam; Mohammed E Rashid; Khaleda Akhter; Abedalla Abdelghani; Hamzah A Babkair; Mohammed G Sghaireen (Wolters Kluwer Medknow Publications, 2024)
Background: Temporomandibular joint disorders (TMDs) encompass a range of clinical conditions affecting the temporomandibular joint (TMJ) and associated structures. Management approaches for TMDs vary and include both surgical and non-surgical interventions. Materials and Methods: In this retrospective cohort study, medical records of 150 patients diagnosed with TMDs were reviewed. Patients were categorized into two groups: surgical intervention and non-surgical intervention. The surgical group underwent various surgical procedures, including arthroscopy, arthroplasty, and joint replacement, while the non-surgical group received conservative treatments such as physical therapy, pharmacotherapy, and occlusal splints. Pain levels, TMJ function, quality of life (QoL), and patient satisfaction were assessed at baseline and post-treatment (6 months and 1 year). Results: At the 6-month follow-up, both groups experienced a significant reduction in pain scores (surgical group: 6.3 ± 1.2 to 2.4 ± 0.9, non-surgical group: 6.1 ± 1.1 to 3.2 ± 1.0). TMJ function improved in both groups (surgical group: 2.5 ± 0.8 to 4.8 ± 0.6, non-surgical group: 2.6 ± 0.7 to 4.2 ± 0.9). QoL scores increased (surgical group: 35.2 ± 4.6 to 50.3 ± 5.1, non-surgical group: 35.5 ± 4.2 to 45.7 ± 4.8), and patient satisfaction rates were high (surgical group: 92%, non-surgical group: 87%) at the 1-year follow-up. Conclusion: Both surgical and non-surgical management approaches demonstrated significant improvements in pain relief, TMJ function, QoL, and patient satisfaction for individuals with TMDs.